Bank interest rates in a small European economy: Some exploratory macro level analyses using Finnish data - Karlo Kauko (Bank of Finland, 2005)
This paper presents econometric analyses on the determination of bank deposit and lending rates using longitudinal Finnish data. Interest rate pass-through is very strong, possibly complete, in the case of lending rates; in the case of deposit rates the pass-through is far from complete, even in the long term.The monetary union has benefited customers by decreasing the average rate on new loans.Credit and interest rate risk premiums are clearly observable in banks' lending rates.The impact of money market rates on loan stock rates seems to have been non-linear; no obvious explanation for this phenomenon has been found.
URN:NBN:fi:bof-20140807144
Keywords: G21; E43; E44; 330; banking; interest rates